2013
DOI: 10.1371/journal.pone.0063101
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipid and Cholesterol Induce Ovarian Dysfunction and Abnormal LH Response to Stimulation in Rabbits

Abstract: Background/AimExcess of fat intake is dramatically increasing in women of childbearing age and results in numerous health complications, including reproductive disorders. Using rabbit does as a biomedical model, the aim of this study was to evaluate onset of puberty, endocrine responses to stimulation and ovarian follicular maturation in females fed a high fat high cholesterol diet (HH diet) from 10 weeks of age (i.e., 2 weeks before normal onset of puberty) or a control diet (C diet).Methodology/Principal Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 57 publications
3
39
0
Order By: Relevance
“…Furthermore, hypertrophy and dysfunction of the visceral adipose tissue (VAT) have been associated with ovarian failure [35], suggesting an influence of periovarian environment in the follicles maturation. Other studies conducted in domestic and laboratory animals have confirmed that alterations in metabolism affect the ovarian function [69]. …”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, hypertrophy and dysfunction of the visceral adipose tissue (VAT) have been associated with ovarian failure [35], suggesting an influence of periovarian environment in the follicles maturation. Other studies conducted in domestic and laboratory animals have confirmed that alterations in metabolism affect the ovarian function [69]. …”
Section: Introductionmentioning
confidence: 86%
“…; Cordier et al. ). As in our results, it was previously shown in rabbit does that hypercholesterolaemic and hyperlipidic diet led to foetal growth differences between groups, with the main differences found at the term of gestation (days 27 and 28) (Picone et al.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, maternal hyperlipidaemia alone may be sufficient to induce impairment to fetal growth. Using a rabbit model (Picone et al 2011;Cordier et al 2013) a high fat diet did not induce weight gain due to appetite compensation but altered lipid metabolism, hormonal reproductive function and follicular growth in the mother and triggered abnormal placental vascularisation and IUGR in the fetus. Postnatally, offspring displayed increased adiposity, weight gain and hypertension similar to other rodent models mentioned above.…”
Section: Lipid Metabolism and Fatty Acid Signallingmentioning
confidence: 99%
“…Deficiency of perilipin-2 can protect against dietaryinduced obesity and its consequences. Thus, its overexpression in early embryos as a consequence of a hyperlipidic environment may indicate a first sign of later weight gain and appetite dysregulation (Picone et al 2011;Cordier et al 2013;McManaman et al 2013). …”
Section: Lipid Metabolism and Fatty Acid Signallingmentioning
confidence: 99%